A robust on-demand routing protocol for cognitive radio ad hoc networks - Che-Aron, Zamree; Hassan Abdalla Hashim, Aisha; Abdullah, Khaizuran; Hassan, Wan Haslina; Rahman, Md. Arafatur (Springer International Publishing, 2015)
Cognitive Radio (CR) technology has been introduced to solve the problems of spectrum underutilization and spectrum scarcity caused by improper spectrum management policies. In Cognitive Radio Ad Hoc Networks (CRAHNs), which operate without centralized infrastructure support, data routing encounters various challenges including frequent topology changes, heterogeneous spectrum availability, and intermittent connectivity caused by the activities of Primary Users (PUs). In this paper, a robust on-demand routing protocol for CRAHNs, referred to the Robustness Aware Cognitive Ad-hoc Routing Protocol (RACARP), is proposed with an aim to provide robust paths for data delivery. The Expected Path Delay (EPD) routing metric used for path decision is introduced and applied in the protocol. The metric takes account of the link delay and the effect of packet loss on wireless links. Furthermore, the protocol avoids creating a transmission path that uses PU’s channel in PU regions in order to counteract the impact of PU activities which can simply cause communication interruptions. The protocol also jointly exploits path and spectrum diversity in routing process in order to provide multi-path and multi-channel routes for the purpose of fast route recovery. The performance evaluation is conducted through simulation using NS-2 simulator. The simulation results prove that the RACARP protocol achieves better performance in terms of average throughput and average end-to-end delay as compared to the Dual Diversity Cognitive Ad-hoc Routing Protocol (D2CARP).